1971
DOI: 10.1084/jem.133.4.740
|View full text |Cite
|
Sign up to set email alerts
|

On the Number and Nature of Antigen-Sensitive Lymphocytes in the Blood of Delayed-Hypersensitive Human Donors

Abstract: Considerable progress in our understanding of the basic mechanisms of delayedtype hypersensitivity has been made in recent years, largely as a consequence of studies in vitro (1, 2). Although most of these studies have approached the problem primarily at the phenomenological level, they have established that the immunological information necessary for the initiation of cell-mediated immune reactions in vitro is possessed by the small lymphocyte which, upon interaction with specific antigens can influence, dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

1972
1972
1979
1979

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 25 publications
(26 reference statements)
1
22
0
Order By: Relevance
“…In the latter animals CL were calculated to be 0.5 % in lymph nodes and 0.3 % in spleens and peripheral blood. The calculated number tallies well with the calculated number of effector cells in lymphoid tissues of guinea pigs (37) and in peripheral blood of humans (38) with delayed hypersensitivity. Henney determined a similar small number per II-2 antigen in sensitized mice (18), as did Brunner (39) (36) by measuring uptake of thymidine-3H.…”
Section: Discussionsupporting
confidence: 65%
“…In the latter animals CL were calculated to be 0.5 % in lymph nodes and 0.3 % in spleens and peripheral blood. The calculated number tallies well with the calculated number of effector cells in lymphoid tissues of guinea pigs (37) and in peripheral blood of humans (38) with delayed hypersensitivity. Henney determined a similar small number per II-2 antigen in sensitized mice (18), as did Brunner (39) (36) by measuring uptake of thymidine-3H.…”
Section: Discussionsupporting
confidence: 65%
“…The immuni zation procedure would, in the first instance, induce proliferation of the antigen responsive lymphocytes and eventually result in the production of an effector cell, which could be a non-dividing, MIF producing T-lymphocyte which comes nevertheless from a dividing cell precursor. The vi rus plaque assay of Jimenez et al [5] would be an illustration of this.…”
Section: Discussionmentioning
confidence: 99%
“…Hayry and Andersson (12) also found that the formation of large lymphoid cells after restimulation of long-term MLC cells with the relevant alloantigens was unaffected by the presence of hydroxyurea, an inhibitor of DNA synthesis, but no data on CTL function under such conditions were reported . Using a virus plaque assay, Jimenez et al (13) observed that the antigen-dependent activation of presumably immune T cells was unaffected by the presence of a mitotic inhibitor . More recently, the differentiation of mitogen-stimulated B lymphocytes into functional antibody-producing cells in the absence of DNA synthesis has been demonstrated by Andersson and Melchers (14) .…”
Section: Discussionmentioning
confidence: 99%